Capillary transport of water in cracked and non-cracked UHPFRC specimens - Matos, Ana Mafalda (2019)
The primary goal of the present paper is to investigate the influence of cracking on water transport by capillary suction of UHPFRC. Prismatic specimens were firstly loaded under four-point bending up to a specific crack open displacement (COD). Target COD, under loading, was varied between 200 and 400 µm, in steps of 50 µm. After unloading, a COD recovery was observed with residual COD ranging between 116-334 µm and 75-248 µm for UHPFRC-1.5% and UHPFRC-3.0% specimens, respectively. The crack pattern created was characterised (number of cracks and crack width) befora capillarity testing. Sorptivity results of cracked UFPFRC-1.5% and UFPFRC-3.0% specimens remained in the range of 0.024 to 0.044 mg/(mm2.min0.5), which are about 2 to 4 times higher than the sorptivity results of non-cracked UHPFRC specimens. However, the maximum sptorvity observed on cracked UHPFRC is relatvely low as compared to typical sorptivity resuts found in good quality conventional concrete or engineered cementitious composites (ECC).